Assessment of the phytoreclamation of an oil-contaminated soil cultivated with “Cynodon dactylon, Eleusine indica” and “Eragrostis tenela” - Beckley IKHAJIAGBE; Boniface O. EDEGBAI; Gloria O. OMOREGIE; Amenze M. EWEKA (Studia Universitatis Babeș-Bolyai. Biologia)
The interactions between Cynodon dactylon, Eragrostis tenela and Eleusine indica in the phytoremediation of petroleum hydrocarbon were investigated. Top soil was collected from a marked plot and polluted with spent engine oil (SEO) to obtain a constant 5% w/w concentration. Thereafter, the soils were sown with Cynodon dactylon, Eragrostis tenela and Eleusine indica singly and in combination of two’s and three’s in separate bowls. The set up was left for three (3) months in a screen house. The results revealed that there were reductions in soil concentrations of total petroleum hydrocarbons, from 26523.76 mg/kg to 19959 mg/kg in the oil-polluted soil. Bacillus subtilis, Micrococcus sp., Proteus vulgaris were the prevalent bacteria species found in the soils, while prevalence fungi species included Aspergillus niger, Geotricium sp., Penicillium sp., Rhizopus sp., Aspergillus flavus, and Fusarium solani. Morphological parameters of the three grasses were better enhanced when sown singly than when they were in combinations of two’s and three’s. Remediation was however best when they were sown altogether as one.